Analysis of the adverse events following immunization with inactivated quadrivalent influenza vaccine from 2018 to 2020 in Zhejiang province, with a comparison to trivalent influenza vaccine - Huakun Lv; Xuejiao Pan; Hui Liang; Ying Wang; Yu Hu (Taylor & Francis Group, 2021)
Objectives To summarize reports to the national adverse event following immunization surveillance system (NAEFISS) following inactivated quadrivalent influenza vaccine (QIV) in Zhejiang province from 2018 to 2020. Methods We analyzed adverse events following immunization (AEFI) reports following QIV, with a comparison, with the AEFI reports following inactivated trivalent influenza vaccine (TIV). Reporting rates of AEFI were calculated by age, severity of AEFI, categories of AEFI, and reaction categories. The data mining algorithm used in this study was reporting odds ratio (ROR). A value of ROR‑1.96SE >1 (standard error [SE]) was considered as positive signal. These reporting rates between vaccine types were compared through chi-square tests. Results NAEFISS received 514 AEFI reports following QIV and 536 reports following TIV, with a reporting rate of 13.66/100,000 100,000 doses/100,000 doses (χ2 = 7.11, P> .05). Of the 514 reports following QIV, 410 were vaccine product-related reactions and 51 were severe AEFI. Fever/redness/induration was the most frequent clinical diagnosis of the QIV AEFI, with a reporting rate of 12.42/100,000 doses in the age group of 3-17 years, and 12.44/100,000 doses in the age group of ≥18 years. The positive signal of QIV AEFI was observed for the allergic rash and asthma/wheezing. Conclusion The present analysis did not identify any new/unexpected safety concerns. We suggested that NAEFISS continue to monitor the safety of QIV.